Fighting Against Climate Change to Build Positive Peace: Proposal of an Intersectional Panel on Environmental Peacebuilding in Sudan (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
Sudan has a long history of conflicts between the central Nile valley and those peripheral regions in the West, South, and North. Climate change effects exacerbate the violent situation in Sudan due to erratic rainfall, longer dry spells, and more frequent floods, which shortens sharply the supply of human basic needs and economic resources.Relying on the thinking of the consequences of climate change in peacebuilding, I will argue that combating climate change can contribute to peacebuilding in Sudan. The intervention is an intersectional panel that combines both top-down government-led initiatives to build stability and bottom-top civil society led initiatives to build both negative and positive peace and to decolonize peacebuilding in Sudan via combating climate change. The theory of this proposal is based on environmental peacebuilding that environmental challenges encountered by parties in conflict can be turned into cooperation and peace opportunities for them. With a one-way fixed effects model data analysis, it shows evidence that combating climate change can contribute to peacebuilding.
Keywords: Environmental Peacebuilding; Climate Change; Decolonizing Peacebuilding; One-way fixed effects model